(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2021)
I have proved in [3], on May 2018, the Goldbach (1690-1764) binary conjecture, remained open since 1742, saying that any even integer greater than 4 is the sum of two prime integers , by using the Schoenfeld (1920-2002) inequality [9] showed by myself, on April 2017, in [4]. Now I confirm the Goldbach conjecture by using, essentially, some topological properties of the Integer part function